"On being Scientific in Preparation of Articles" - Kulkarni, P. D.; Ratnalekar, N. V. (Journal of Engineering Education Transformations, 1995)
Purpose of This Article The Journal of Engineering Education has for the last few years provided a forum for researchers and practitioners in the field of Engineering Education to express their ideas and views about the field.